2015
DOI: 10.4012/dmj.2014-066
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface treatment of contaminated zirconia on surface free energy and resin cement bonding

Abstract: Influences of contamination and cleaning methods on the bonding of resin cement to zirconia ceramics were examined. Airborne particle-abraded zirconia (IPS e.max ZirCAD) specimens were contaminated with saliva and cleaned with tap water (SC) or by application of 37% phosphoric acid (PA), Ivoclean (IC), or additional airborne particle abrasion (AB). Specimens without contamination served as controls. After application of Monobond Plus to the surface of the specimens, resin cement was mixed and inserted into a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(130 citation statements)
references
References 19 publications
10
115
0
5
Order By: Relevance
“…It has been reported that the γ S d values of oxidized surfaces measured using this method were approximately 40 mN/m 18,20) , whereas those of surfaces coated with polytetrafluoroethylene were approximately 20 mN/m. The total surface free energy, γ S p , and γS h values of the SC group were significantly lower than those of the control, TE and CE groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the γ S d values of oxidized surfaces measured using this method were approximately 40 mN/m 18,20) , whereas those of surfaces coated with polytetrafluoroethylene were approximately 20 mN/m. The total surface free energy, γ S p , and γS h values of the SC group were significantly lower than those of the control, TE and CE groups.…”
Section: Resultsmentioning
confidence: 99%
“…The wettability of the surface is important for 18) . The strength of the bond between the ceramic and the resin depends on several factors, including the surface treatment of ceramics and the ability of the resin to wet the bonding surface 6) .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of surface contamination with saliva and subsequent cleaning with phosphoric acid has been described 11,12) and the authors recommend that restorations be sandblasted to increase bonding effectiveness. To clean the bonding surface of restoration, ultrasonic cleaning, which is safe and easy, is frequently 13,14) .…”
Section: Introductionmentioning
confidence: 99%
“…Sandblasting also increases surface roughness as well as surface area and surface energy, thus making it possible to achieve stronger mechanical durability of the restoration. Moreover, it can also increase wettability of resin cements or silane primers [20,21]. …”
Section: Discussionmentioning
confidence: 99%